2012
DOI: 10.1016/j.vaccine.2012.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the vaccination campaign against A(H1N1) influenza in pregnant women in France: Results from a national survey

Abstract: Background and objective: Pregnant women were a priority group for vaccination during the 2009 A(H1N1) influenza pandemic. In France, vaccination was organized in ad hoc centers. Women received vouchers by mail and were given a non-adjuvanted vaccine. Our objective was to assess the national vaccination rate among pregnant women and to determine the association of vaccination with maternal characteristics, prenatal care, and pregnancy-related health behaviors. Method: Data came from a national representative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
26
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
10
26
3
Order By: Relevance
“…In line with previous studies, we found that younger pregnant women were less likely to have been vaccinated 13,19,32 . This phenomenon occurred not only in pregnant women but also in other groups, such as hospital workers and the general population 14 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In line with previous studies, we found that younger pregnant women were less likely to have been vaccinated 13,19,32 . This phenomenon occurred not only in pregnant women but also in other groups, such as hospital workers and the general population 14 .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, studies performed in developed countries showed better results than the former countries but still below the values reached in Brazil. In France, Blondel et al 19 found 29.3%, in the USA, Centers for Disease Control and Prevention (CDC) 23 found a rate of 40.4%, in the Netherlands 24 63% and in Canada 25 76.4%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations